Bringing a building into being: A Virtual Reality Application as a non-traditional research output. Issue 2 (1st September 2022) - Westin, Jonathan; Almevik, Gunnar
This article sets out from the digital reconstruction of a historic building and assesses and discusses the use of a Virtual Reality Application as a self-standing research output. Despite the recognized possibilities and the amount of research that goes into the creation of scientific virtual reconstructions, there is still a need for broadly accepted procedures to not only publish them but also incorporate them into the academic systems as research outputs in their own right. The empirical material ‐ a digital reconstruction of a wooden stave church ‐ is here explored as both a hermeneutic device in the research process and a research output. We argue that the use of technology such as virtual reality that can communicate presence is particularly important in research on embodied craft skills and sensory-based judgements to reduce the loss of information in translations between modes, medias and formats. However, to function and have an impact as a research output, new formats have to adapt to fundamental and broadly accepted conventions within academia which have been established by the text-on-paper formats and establish conventions that facilitate access, navigation and referencing.